Diagnostic challenge for giant left retroperitoneal accessory spleen: a case report. Issue 2 (October 2020) - Li, Youjian; Qiu, Xuefeng; Li, Weijian; Guo, Hongqian; Li, Xiaogong
An accessory spleen refers to single or multiple splenic tissues that appear outside the normal spleen position and have structures and functions similar to those of a normal spleen. We herein present a rare case of a 31-year-old woman who was hospitalized because of a 14-year history of sudden left upper abdominal pain after running. Abdominal computed tomography suggested a large soft tissue mass at the left renal hilum surrounded by several enlarged lymph nodes, which was totally different from computed tomography scanning of normal accessory spleen. The mass was resected by robot-assisted laparoscopic surgery. Histopathological examination confirmed the diagnosis of accessory spleen. The incidence of retroperitoneal accessory spleen is very rare, which should be differentiated with retroperitoneal tumors.